Standardization of image reconstruction parameters for dynamic fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography. Issue 12 (December 2018) - Sharma, Akshima; Pandey, Anil K.; Mohan, Anant; Bhalla, Ashu S.; Vishnubhatla, Sreenivas; Sharma, Mehar C.; Jain, Deepali; Thulkar, Sanjay; Gupta, Priyanka; Bal, Chandra S.; Kumar, Rakesh
Abstract : Aim: The present study aimed to standardize the ordered subset expectation maximization (OSEM) reconstruction parameters for a dynamic PET/CT study. Participants and methods: A locally fabricated phantom was filled with fluorine-18-fluorodeoxyglucose ( 18 F-FDG) for four different sphere to background ratios (SBRs), that is, 10 : 1, 8 : 1, 6 : 1, and 4 : 1, and dynamic PET/CT was acquired for 5 min. Transaxial slices were reconstructed using OSEM [full-width at half-maximum (FWHM): 1–7 mm and iterations: 1–8]. Two nuclear medicine physicians visually rated image quality on the basis of the following criteria: score 1: poor quality, score 2: average quality, and score 3: good quality. The quantitative assessment of image quality was performed on the basis of the calculation of noise, horizontal, and vertical line profiles. The standardized parameters were applied to the PET/CT study of seven non-small-cell lung cancer patients, and their image quality was compared with the vendor-provided default parameters. Results: In the phantom study, for SBR 10 : 1, the images reconstructed with FWHM 4 mm and four iterations, for SBR 8 : 1 and 6 : 1, the image with FWHM 3 mm and five iterations, and for SBR 4 : 1, the image with FWHM 2 mm and five iterations were found to have the best quality. In the patient study, FWHM 4 mm and four iterations were found to be suitable for the reconstruction of dynamic 18 F-FDG PET/CT studies with a tumor to background ratio of 10 : 1. With an increase in iterations, noise and sharpness in the image increased, whereas with an increase in FWHM, the image became smoother. Conclusion: The standardized reconstruction parameters of OSEM for the dynamic PET/CT study were found to be 4-mm filter FWHM and four iterations in SBR 10 : 1.